The Anti-Virulence Activities of the Antihypertensive Drug Propranolol in Light of Its Anti-Quorum Sensing Effects against Pseudomonas aeruginosa and Serratia marcescens - Hadil Faris Alotaibi; Haifa Alotaibi; Khaled M. Darwish; El-Sayed Khafagy; Amr S. Abu Lila; Mohamed A. M. Ali; Wael A. H. Hegazy; Samar Zuhair Alshawwa (Biomedicines, 2023)
The development of bacterial resistance is an increasing global concern that requires discovering new antibacterial agents and strategies. Bacterial quorum sensing (QS) systems play important roles in controlling bacterial virulence, and their targeting could lead to diminishing bacterial pathogenesis. In this context, targeting QS systems without significant influence on bacterial growth is assumed as a promising strategy to overcome resistance development. This study aimed at evaluating the anti-QS and anti-virulence activities of the β-adrenoreceptor antagonist propranolol at sub-minimal inhibitory concentrations (sub-MIC) against two Gram-negative bacterial models Pseudomonas aeruginosa and Serratia marcescens. The effect of propranolol on the expression of QS-encoding genes was evaluated. Additionally, the affinity of propranolol to QS receptors was virtually attested. The influence of propranolol at sub-MIC on biofilm formation, motility, and production of virulent factors was conducted. The outcomes of the propranolol combination with different antibiotics were assessed. Finally, the in vivo protection assay in mice was performed to assess propranolol’s effect on lessening the bacterial pathogenesis. The current findings emphasized the significant ability of propranolol at sub-MIC to reduce the formation of biofilms, motility, and production of virulence factors. In addition, propranolol at sub-MIC decreased the capacity of tested bacteria to induce pathogenesis in mice. Furthermore, propranolol significantly downregulated the QS-encoding genes and showed significant affinity to QS receptors. Finally, propranolol at sub-MIC synergistically decreased the MICs of different antibiotics against tested bacteria. In conclusion, propranolol might serve as a plausible adjuvant therapy with antibiotics for the treatment of serious bacterial infections after further pharmacological and pharmaceutical studies.